INTENSITAS BERMAIN GAME ONLINE TERHADAP POLA AKTIVITAS FISIK SISWA SMP ADVENT MENIA, KABUPATEN SABU, RAI JUA, NTT - David Raymond Ludjileo (Jurnal Skolastik Keperawatan, 2020)
Introduction: Addiction to online games can affect physical health, social relations, cause physical weakness as a result of reduced sleep hours, uneven nutrition and can lead to dehydration. And lazy to do physical activities such as sports. Objective: This study aims to assess the effect of the intensity of playing online games on the patterns of physical activity of students. Methods: This study was a descriptive correlation study with the population of Advent Menia Junior High School students, Sabu Rai Jua District, NTT totaling 46 students and the sample was recruited with saturated sampling techniques. Results: data shows that 80% are in the low intensity category of online game play and 20% in the moderate category. 80% have low physical activity patterns and 20% have moderate physical activity patterns. There is a significant relationship between the intensity of playing online games with physical activity patterns. Discussion: Community nursing care in the prevention of obesity and addiction to online games in adolescents can be a consideration in service to the community and the focus of subsequent research.